Evaluation of an agricultural extension program in the Colombian cocoa sector - Herrán Ramírez, Lorena Andrea (2025)
Sourcing raw materials in a more inclusive and participatory manner while seeking development for the different actors involved, has become a priority for agribusiness companies. In Colombia, among the programs focused on promoting cocoa sustainability, Companía Nacional de Chocolates (CNCh in Spanish) has been supporting Colombian farmers for more than 65 years, encouraging national production and providing support through its team of professionals. The objective of this research was to develop a monitoring and evaluation model for CNCh’s extension program through a process of co-creation with stakeholders to identify opportunities for improvement. A mixed study with both a qualitative approach, oriented from an interpretivist theoretical perspective, and a quantitative approach, framed from a descriptive analysis, was conducted to analyze the documents containing information related to the extension program, surveys, semi-structured interviews and focus groups, to finally design and validate six instruments that complemented the final result: the extension program’s monitoring and evaluation models. The results of this study indicated that CNCh offers intervention strategies that seek the sustainability of cocoa farmers; however, there are opportunities for improvement in terms of the number of professionals, the number of visits to each public-private alliance, and the technical monitoring conducted of the associations of cocoa producers. This is reflected in a lack of monitoring and evaluation of the strategies carried out.